PERBANDINGAN PROFIL TOTAL DNA DURIAN (Durio zibethinus Murr) VARIETAS MENOREH KUNING HASIL ISOLASI DENGAN METODE DETERGEN DAN KIT KOMERSIAL - Tara Puri Ducha Rahmani; Budi Setiadi Daryono; Ismail Ismail (Teknosains, 2022)
Menoreh Kuning Durian (Durio zibethinus Murr) cultivar is originated from Dusun Promasan, Banjaroyo Village, Kalibawang Subdistrict, Kulonprogo Regency, Province of Yogyakarta, Indonesia. Durian seller usually claimed their durian to be Menoreh Kuning. Therefore, an accurate method is needed to identify that cultivar. One of the most accurate methods is DNA isolation as the first step. This research was aimed to compare the total DNA profile of Menoreh Kuning Durian using detergent and commercial kit (NucleonTM PhytopureTM Genomic DNA Extraction Kits) qualitatively and quantitatively. The method used in this research was DNA isolation method using detergent and commercial kit (NucleonTM PhytopureTM Genomic DNA Extraction Kits). DNA source came from leaves Menoreh Kuning Durian. DNA pellet then was dissolved in 50 µL TE, after that each of 5 µL sampel was electrophoresized in 1 % of agarose for 30 minutes. The result of eletcrophoresis then was stained with ethidium bromide and finally was observed under transluminator-UV. The results of both isolation methods were compared based on the total DNA profil after electrophoresis, total mass of DNA pellet, and the result of DNA Optical Density. The research result had shown that the DNA of Menoreh Kuning Durian isolated using detergent and commercial kit can be observed under transluminator-UV. The mass of DNA pellet isolated using detergent was 0,004 gram while using kit was 0,0004 gram. The Optical Density results for DNA isolated using detergent were 2,658 AU of Absorbance, Ratio of 1,057, Concentration of 6645,6 µ gr/mL, and Protein of 93,9 milligram/mL. As for the DNA isolated using commercial kit had shown the Optical Density results of 2,760 AU for Absorbance, Ratio of 1,339, concentration of 6900,6 µ gr/mL, and Protein of 54,8 milligram/mL. Based on the research result, can be concluded that the DNA of Menoreh Kuning Durian can be isolated using detergent and commercial kit. The DNA profile isolated using commercial kit had shown a better result than the DNA profile isolated using detergent.